The effect of the dimensions of strategic change on organizational performance level - Abbas G. Atiyah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study examines the nature of the impact of strategic change with its dimensions (business process reengineering, business restructuring, business innovation), and organizational performance with its dimensions (financial performance, Customer satisfaction, Learning and growth) and this study applied in (51) managers, they are (department managers, division managers, and unit managers). The questionnaire was used as a main tool for collecting data and statistical tools to extract, test and analyse results. Based on the findings of the research, a number of recommendations were made, The most important of these was the need for the management's attention in the factory to take the dimensions of strategic change in a better manner, as well as assigning a unit in the factory concerned with the management of strategic change and diagnosing the size of the imbalance and nature of the required strategic change.